2018
DOI: 10.1080/15384047.2018.1507666
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the efficacy of glycolytic blockade in cancer cellsviaRAD51 inhibition

Abstract: Combination therapy targeting glycolysis and specific RAD51 function shows increased efficacy as compared to standard of care treatments in leukemias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Hence, inhibition of the first and middle steps of glycolysis results in reduced cytokine production by bona fide Th1 cells during infection and had no impact on Tr1 cells, suggesting that IL-27 signalling regulates glycolysis specifically in Th1 cells. Blocking glycolysis can reduce disease severity in inflammatory environments such as those found in arthritis [ 74 , 75 ], cancer [ 76 ], autoimmunity [ 77 ] and infections [ 48 ]. Our findings presented here highlight the importance of understanding the metabolic changes that occur during inflammation and how these pathways could potentially be targeted to restore functionality to tissues affected by inflammatory-mediated damage.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, inhibition of the first and middle steps of glycolysis results in reduced cytokine production by bona fide Th1 cells during infection and had no impact on Tr1 cells, suggesting that IL-27 signalling regulates glycolysis specifically in Th1 cells. Blocking glycolysis can reduce disease severity in inflammatory environments such as those found in arthritis [ 74 , 75 ], cancer [ 76 ], autoimmunity [ 77 ] and infections [ 48 ]. Our findings presented here highlight the importance of understanding the metabolic changes that occur during inflammation and how these pathways could potentially be targeted to restore functionality to tissues affected by inflammatory-mediated damage.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been found that DIDS is able to inhibit another polynucleotide binding protein, RAD51, a DNA recombinase essential for double-strand break repair in eukaryotes, and has been investigated as an anticancer agent. 50 Although both the potency and specificity are not sufficient to further pursue DIDS for therapeutic potential, it may prove useful as a tool compound in determining molecular mechanisms of MSUT2-induced tau toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Our 2DG studies in SJL/J mice were primarily conducted to test to what extent this toxic chemotherapeutic could have reduced adverse effects when combined with other compounds. At doses that did not elicit adverse effects, 2DG alone given to mice with a SJL/J background was able to significantly shrink tumors [37]. However, the tumors develop resistance to 2DG after four weeks, after which the tumor growth re-emerges [37].…”
Section: Introductionmentioning
confidence: 98%
“…At doses that did not elicit adverse effects, 2DG alone given to mice with a SJL/J background was able to significantly shrink tumors [37]. However, the tumors develop resistance to 2DG after four weeks, after which the tumor growth re-emerges [37]. Although the penetrance of spontaneous tumorigenesis in SJL/J is >95%, the time it takes to develop such tumors is ~one year, with a range between nine months to 1.2 years [24].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation